Physical Characteristics of Organic Fertilizer Based on Banana Corm and Frond Variations - Dian Nugraheni; Khalis Nadhira Santosa; Nina Chairani Fatimah; Rosita Assyifa Purba; Abraham Tiandno Witjaksono; Hanandya Rahma Dinda Destriani; Eka Nurul Qomaliyah; Himawan Ganjar Prabowo (Asian Journal of Environmental Research, 2025)
This study aims to determine the effect of variations in banana corm and banana fronds on the odor and physical properties of solid organic fertilizer made from household waste. In addition, the research also aims to identify the differences in odor and physical characteristics between solid organic fertilizer based on EM4 and that based on banana corm and fronds. The method used is an experimental approach to test the effectiveness of organic fertilizers produced from different raw materials: banana corm, banana frond, rice-washing water, and household waste (predominantly rotten tape). The first treatment used a mixture of banana corm, banana fronds, rice-washing water, and household waste in a 1:1:1:1 ratio. The second treatment consisted of banana fronds, rice-washing water, and household waste in a 1:1:1 ratio. The third treatment included banana corm, rice-washing water, and household waste, also in a 1:1:1 ratio. The fourth treatment used EM4, rice-washing water, and household waste in a ½:1:1 ratio. The results showed that on the first day, all treatments emitted a strong odor of tape and household waste. Over time, an acidic smell began to emerge, eventually turning into a fresh, earthy scent, particularly in treatments with banana corm and EM4. The color of the fertilizer changed from dark brown to blackish brown, indicating successful decomposition. The texture also changed from coarse to more crumbly and homogeneous. The treatment with EM4 showed faster fermentation and a more stable odor compared to the other treatments.